Exemplifying endophytes of banana (Musa paradisiaca) for their potential role in growth stimulation and management of Fusarium oxysporum f. sp cubense causing panama wilt - Savani, Ajit Kumar; Bhattacharyya, Ashok; Boro, Robin Chandra; Dinesh, K; Jc, Nanjunda Swamy (Folia microbiologica, 2021)
In the present study, potentiality of endophytic microorganisms such as Rigidiporus vinctus AAU EF, Trichoderma reesei UH EF, and Sphingobacterium tabacisoli UH EB in the management of panama wilt and growth promotion of banana was assessed through artificial inoculation. During the study, a total of 220 bacterial and 110 fungal endophytes were isolated from root, pseudostem, and leaf samples of banana, and they were evaluated against Fusarium oxysporum f. sp cubense causing panama wilt. Out of total 330 bacterial and fungal endophytes, only five endophytes exhibited antagonism against Fusarium oxysporum f. sp cubense, out of which only three isolates, namely Trichoderma reesei UH EF, Rigidiporus vinctus AAU EF, and Sphingobacterium tabacisoli UH EB, produced indole acetic acid, siderophore, and hydrogen cyanide, except one bacterial strain Sphingobacterium tabacisoli UH EB which does not produce hydrogen cyanide. Furthermore, these three endophytes were identified through cultural and morphological characteristics as well as by the sequencing internal transcribed spacer (ITS) and 16S rRNA gene sequences analysis for bacteria, respectively. The response of host plant to endophyte inoculation was assessed by measuring the change in four growth parameters; plant height, pseudo stem girth (diameter), number of roots, and total number of leaves. The application of endophytes, irrespective of isolate and treatment type promoted the overall growth of the plant growth when compared with diseased plants with significant higher values recorded for all parameters assessed. The endophytes reported as growth promoters were found to have significant inhibition effect on Foc which can evidenced with lowest AUDPC values and epidemic rate at 99.09 units2 and 0.02 unit/day, respectively.
Keywords: Hypocreales; Fusarium; banánovník; Sphingobacterium; nemoci rostlin; endofyty; RNA, Ribosomal, 16S; mikrobiální interakce; RNA ribozomální 16S; Polyporales; Plant Diseases; Musa; Endophytes; Microbial Interactions